2006
DOI: 10.1093/eurheartj/ehi735
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of nebivolol in elderly heart failure patients with or without systolic left ventricular dysfunction: results of the SENIORS echocardiographic substudy

Abstract: In patients with heart failure and advanced systolic LV dysfunction, nebivolol reduces ventricular size and improves EF. The absence of detectable changes with standard echocardiography in patients with predominant diastolic heart failure questions the mechanism of benefit on morbidity/mortality in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 38 publications
1
44
0
3
Order By: Relevance
“…Patrianakos et al [9] have showed that DT was similarly prolonged with Abdullah Dogan et al, Carvedilol or nebivolol in diastolic dysfunction both study drugs, with earlier improvement with carvedilol. A 12-month nebivolol therapy resulted in a trend toward reduction in mitral E/A ratio and prolongation in DT in elderly HF patients in echocardiographic substudy of SENIORS study [8]. These useful effects may be due to vasodilatory action of both agents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Patrianakos et al [9] have showed that DT was similarly prolonged with Abdullah Dogan et al, Carvedilol or nebivolol in diastolic dysfunction both study drugs, with earlier improvement with carvedilol. A 12-month nebivolol therapy resulted in a trend toward reduction in mitral E/A ratio and prolongation in DT in elderly HF patients in echocardiographic substudy of SENIORS study [8]. These useful effects may be due to vasodilatory action of both agents.…”
Section: Discussionmentioning
confidence: 96%
“…These useful effects are frequently attributed to the elevated LVEF due to reduction in LV volumes [8,9,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These same mechanisms could explain part of the benefit observed in the SENIOR study in patients with chronic heart failure [65].…”
Section: New Paradigm: the Importance Of β3 Receptormentioning
confidence: 79%
“…Outcomes and Rehospitalization in Seniors with Heart Failure) [65] enrolled patients with heart failure, and established as inclusion criteria that the patients were 70 years old or older and incorporated a high percentage of women and patients with preserved systolic function. It showed a reduction of 14% in the mortality from all causes, and there were no more adverse effects than with placebo.…”
Section: The Seniors Study (Study Of Effects Of Nebivolol Interventiomentioning
confidence: 99%